Building sustainable alternatives to capitalism and its permanente crises: The case of indigenous peasant organizations of Cuetzalan del Progreso: The case of indigenous peasant organizations of Cuetzalan del Progreso. - Armenta, Wuendy (2020)
The document presents an analysis of the way in which the indigenous peasant organizations located in Cuetzalan del Progreso have face the advances of capital accumulation, building sustainable alternatives that are related to the management of the territory. The analysis is based on field work carried out by de authors, as well as a documentary review. Perspectives are raised form the New Community Rurality and from the Radical Ecological Economics. Finally, it is concluded by highlighting the social attributes and capacities that the maseual have developed over time and that allow them to generate alternatives to capitalism.